Excavating the Hard Drive: Archaeological Research, XML, and 3D Graphics - Milbank, Thomas L. (Tufts Archival Research Center, 2005)
This paper focuses on the X3D XML application of the VRML international 3D graphic standard. It addresses the integration of X3D graphic files into the Perseus XML document management system. And it addresses the creation of a tool to extract and represent graphic elements from multiple files. The tool provides a specific research mechanism for the discovery of embedded graphic data interspersed through a large corpus, for example, allowing an archaeologist to retrieve every cornice from an extensive collection of files without having to open and search each file manually.